2006
DOI: 10.1021/es061277n
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Plume Opacity by Digital Photography

Abstract: The United States Environmental Protection Agency (USEPA) developed Method 9 to describe how plume opacity can be quantified by humans. However, use of observations by humans introduces subjectivity, and is expensive due to semiannual certification requirements of the observers. The Digital Opacity Method (DOM) was developed to quantify plume opacity at lower cost, with improved objectivity, and to provide a digital record. Photographs of plumes were taken with a calibrated digital camera under specified condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…And the challenge to install contrasting backgrounds behind and next to the DDs as needed with DOM's contrast model (Du et al, 2007). The transmission model calculates the plume's opacity based on the radiance from the plume and the radiance from the plume's background.…”
Section: Calculation Of Opacitymentioning
confidence: 99%
See 3 more Smart Citations
“…And the challenge to install contrasting backgrounds behind and next to the DDs as needed with DOM's contrast model (Du et al, 2007). The transmission model calculates the plume's opacity based on the radiance from the plume and the radiance from the plume's background.…”
Section: Calculation Of Opacitymentioning
confidence: 99%
“…Because the camera did not directly measure N t2 , the proportionality coefficient, K, is defined by N t2 = K × N × opacity (Du et al, 2007), and then the plume opacity could be determined by the transmission model as described by…”
Section: Calculation Of Opacitymentioning
confidence: 99%
See 2 more Smart Citations
“…Most recently, DOCS was tested using a range of commercially available cameras in lieu of a specific digital camera that was required to be used for the previous field campaigns (12). Another DSC-based method, digital optical method (DOM), was developed from light transfer principles to quantify plume opacity using commercial-off-the-shelf digital still cameras (13). Testing during daytime demonstrated that DOM provided results that are consistent with Method 9 requirements (14).…”
Section: Introductionmentioning
confidence: 99%